Confirming a predicted selection rule in inelastic neutron scattering spectroscopy: the quantum translator-rotator H2 entrapped inside C60 - Xu, Minzhong; Jiménez-Ruiz, Mónica; Johnson, Mark R.; Rols, Stéphane; Ye, Shufeng; Carravetta, Marina; Denning, Mark S.; Lei, Xuegong; Bačić, Zlatko; Horsewill, Anthony J. (American Physical Society, 2014)
We report an inelastic neutron scattering (INS) study of H2 molecule encapsulated inside the fullerene C60 which confirms the recently predicted selection rule, the first to be established for the INS spectroscopy of aperiodic, discrete molecular compounds. Several transitions from the ground state of para-H2 to certain excited translation-rotation states, forbidden according to the selection rule, are systematically absent from the INS spectra, thus validating the selection rule with a high degree of confidence. Its confirmation sets a precedent, as it runs counter to the widely held view that the INS spectroscopy of molecular compounds is not subject to any selection rules.